Does the Technique for Assessing Loss of Resistance Alter the Magnitude of Epidural Needle Tip Overshoot?. Issue 3 (June 2020) - Cometa, M. Anthony; Lopez, Brandon M.; Vasilopoulos, Terrie; Destephens, Anthony J.; Bigos, André; Lizdas, David E.; Gravenstein, Nikolaus; Lampotang, Samsun
Abstract : Introduction: Postdural puncture headache due to accidental dural puncture is a consequence of excessive needle tip overshoot distance after entering the epidural space via a loss of resistance (LOR) technique. We are not aware of any quantitative comparison of the magnitude of needle tip overshoot (distance traveled by the needle tip beyond the point where LOR can be discerned) for the various LOR assessment techniques that are taught. Such a comparison may provide insight into contributing factors of accidental dural puncture and associated postdural puncture headache. Methods: A custom-built simulator was used to evaluate the following 3 LOR assessment techniques: incremental needle advancement, intermittent LOR assessment (II); continuous needle advancement, high-frequency intermittent LOR assessment (CI); and continuous needle advancement, continuous LOR assessment (CC). Results: There were significant mean differences in maximum overshoot past a virtual LOR plane due to technique ( F (2, 124) = 79.31, P < 0.001) (Fig. 2). Specifically, maximum overshoot was greater with technique II [mean = 3.8 mm, 95% confidence interval (CI) = 3.4–4.3] versus either CC (mean = 1.9 mm, 95% CI = 1.5–1.8, P < 0.001) or CI (mean = 1.4 mm, 95% CI = 0.9–2.3, P < 0.001). Differences in maximum overshoot between CC and CI were not statistically different ( P = 0.996). Maximum overshoot was greater at 4 cm (mean = 3.0 mm, 95% CI = 2.6–3.4) compared with 5 cm (mean = 2.3 mm, 95% CI = 2.0–2.5, P = 0.044), 6 cm (mean = 2.0 mm, 95% CI = 1.9–2.2, P = 0.054), 7 cm (mean = 1.9 mm, 95% CI = 1.7–2.1, P = 0.002), and 8 cm (mean = 1.8 mm, 95% CI = 1.6–2.1, P = 0.001). In addition, maximum overshoot at 5 cm was greater than that at 7 cm ( P = 0.020) and 8 cm ( P = 0.037). The other LOR depths were not statistically significantly different from each other. Depth did not have a significant interaction with technique ( P = 0.517). Technique preference had neither a significant relationship to maximum overshoot ( P = 0.588) nor a significant interaction with LOR assessment technique ( P = 0.689). Discussion: Technique II LOR assessment produced the greatest needle overshoot past the simulated LOR plane after obtaining LOR. This was consistent across all LOR depths. In this bench study, the II technique resulted in the deepest needle tip maximum overshoot. We are in the process of designing a clinical study to collect similar data in patients.